HYDRODYNAMICS ANALYSIS OF JANUS SPHERE AT VARIATIONS OF THE REYNOLDS NUMBER - James Julian; Waridho Iskandar; Fitri Wahyuni (Jurnal Teknologi, 2023)
The hydrodynamics of the homogeneous and Janus spheres were compared computationally at various Reynolds number variations. The Janus sphere is divided into two parts: slippery, which is set as a free-slip wall, and sticky, which is arranged as a free-slip wall. The equation used is the RANS equation for laminar fluid flow. Research focuses more on hydrodynamic forces and visualization of fluid flow by using velocity contours and streamlines. The domains of computational processes are arranged in a rectangular shape. The Richardson Extrapolation method verifies the mesh and gives the result that the meh variation is within the convergence range. Mesh with 105 elements is used for further computation because it only gives the lowest error of 0.129%. Meanwhile, the validation results show that the computational process can follow the experimental results at 0°≤θ≤80°. The Janus sphere is hydrodynamically better than the homogeneous sphere, where the Cl produced is larger and the Cd produced is smaller. The Janus sphere can prevent separation at a Reynolds number of 20 and reduce the recirculation area at a Reynolds number of 50.